1992
DOI: 10.1128/aac.36.9.1978
|View full text |Cite
|
Sign up to set email alerts
|

Activity of amphotericin B cholesterol dispersion (Amphocil) in experimental visceral leishmaniasis

Abstract: Standard therapy of human visceral leishmaniasis with parenteral pentavalent antimonial agents is generally curative but has the disadvantages of a 28-day treatment course, occasional treatment failures, and toxicity.The antifungal and antileishmanial agent amphotericin B has been complexed with lipids to develop a less toxic formulation of amphotericin B. Because lipid particles are phagocytized by the reticuloendothelial system, lipid-associated amphotericin B should be concentrated in infected macrophages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…We also reported the isolation of some non-polar compounds; namely palmitic acid, cerotic acid, tetradecyl acetate, and 24-alpha-methylcholest-5-enol, and a serratane-type triterpene, alpha-onocerin [33,34]. It has been reported that amphotericin B complexed with cholesterol is at least four times more active than amphotericin B alone in L. donovani-infected hamsters [35]. Moreover, some fatty acid derivatives have been reported with antileishmanial and antimalarial activity [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…We also reported the isolation of some non-polar compounds; namely palmitic acid, cerotic acid, tetradecyl acetate, and 24-alpha-methylcholest-5-enol, and a serratane-type triterpene, alpha-onocerin [33,34]. It has been reported that amphotericin B complexed with cholesterol is at least four times more active than amphotericin B alone in L. donovani-infected hamsters [35]. Moreover, some fatty acid derivatives have been reported with antileishmanial and antimalarial activity [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding suggests that amphotericin B, traditionally considered a second-line antileishmanial agent (2,8,11,12), may be worth testing as primary therapy for the T-celldeficient patient with visceral infection. Lipid-associated amphotericin B preparations (3,5,6) may prove even more useful.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we have extended our analysis to two other experimentally and clinically active antileishmanial agents, amphotericin B and pentamidine (3,5,6,8,(11)(12)(13), and tested their efficacies in L. donovani-infected nude mice.…”
mentioning
confidence: 99%
“…Recently, lipid formulations that have lower toxicity have been developed for the treatment of systemic mycoses. 12,14,15 Three commercially available lipid formulations, the liposome AmBisome (NeXtar, San Dimas, CA), the colloidal dispersion Amphocil (Liposome Technology, Inc., Menlo Park, CA), and the lipid complex Abelcet (The Liposome Company, Ltd., London, United Kingdom), have also been shown to be effective against experimental [16][17][18][19] and clinical visceral leishmaniasis, [20][21][22] as well as against experimental cutaneous leishmaniasis. 23 In this study, the experimental activities of these three commercial lipid formulations of amphotericin B were compared with the parent drug, amphotericin B deoxycholate (Fungizone ; E. R. Squibb and Sons, Hounslow, United Kingdom) and the standard drug benznidazole, against experimental infections of T. cruzi in vitro and in vivo.…”
mentioning
confidence: 99%